Balloon overtube-assisted stenting in difficult upper and lower gastrointestinal locations using a modified over-the-wire technique - Pinho, Rolando; Proença, Luísa; Ponte, Ana; Fernandes, Carlos; da Ribeiro, Iolanda; Silva, Joana; Carvalho, João (Endoscopy, 2015)
In this series of four patients, some modifications of the standard over-the-wire (OTW) technique for stent deployment using the balloon overtube normally used in single-balloon enteroscopy are presented. This modified technique allowed the use of OTW stents in patients where there were difficulties that meant the standard technique was unsuccessful. For each patient, the authors describe different small novel adaptations of this modified technique that enabled self-expanding metal stents (SEMSs) and biodegradable stents to be successfully deployed in different gastrointestinal locations. Moreover, in one patient the stent was placed without fluoroscopic guidance.